Customer-Based Brand Equity for Coffee-to-Go Industry: The Influence of Instagram Marketing Through Brand Experience - Zahra Nadhira Khairunnisa; Agus Rahayu; Puspo Dewi Dirgantari; Oce Ridwanudin; Farizki Maulana Rafliansyah (Jurnal Pendidikan Ilmu Sosial, 2024)
The development of information and communication technologies has shifted marketing strategies toward digital methods, one of which is Instagram marketing. Instagram marketing is believed to foster customer-based brand equity within the current coffee-to-go industry market conditions.  This study aims to address gaps in past research, particularly the inconsistent findings and the limited investigation of brand experience as a mediator linking Instagram marketing with customer-based brand equity in the coffee-to-go sector.A quantitative research method with an explanatory survey was employed. The sample consisted of 125 respondents who were consumers of the coffee-to-go industry and had viewed content or Instagram accounts of a coffee-to-go brand. The sampling techniques used were purposive and incidental sampling. All instruments were valid and reliable, and all data met the Classical Assumption Test requirements. Hypothesis testing was conducted using Process Macro by Andrew F. Hayes in SPSS v27. The findings of this study reveal that Instagram marketing positively impacts brand experience; brand experience, in turn, positively affects customer-based brand equity. Additionally, Instagram marketing shows a significant influence on customer-based brand equity, with brand experience serving as a partial mediator in this relationship.